2000
DOI: 10.1007/bf02900731
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin (PCT) in patients with abdominal sepsis

Abstract: Procalcitonin is a new indicator of infection and sepsis. TNF and IL-6 concentrations always rise after major operations and fall in the absence of infection, indicating operative trauma. Procalcitonin is sensitive in detecting infective complications. Under routine conditions the procalcitonin concentrations seems to be valid, reproducible and detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 11 publications
2
39
0
3
Order By: Relevance
“…In spite of this, PCT was described to be more sensitive in sepsis and bacterial infections. [15] Ulus Travma Acil Cerrahi Derg, September 2014, Vol. 20, No.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, PCT was described to be more sensitive in sepsis and bacterial infections. [15] Ulus Travma Acil Cerrahi Derg, September 2014, Vol. 20, No.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been largely confirmed that procalcitonin is the only one in a large array of biochemical markers that closely correlates with the inflammatory host response to microbial infections. 26,27 In peritonitis, only 2 studies 22,23 have ever been conducted, to our knowledge, investigating the usefulness of procalcitonin in monitoring the postoperative course after surgical treatment. Both studies 22,23 have shown that procalcitonin is a reliable indicator of nonsurvival.…”
mentioning
confidence: 99%
“…In contrast, biochemical variables for stratifying disease severity in secondary peritonitis are poorly studied, with inconclusive results due to noncomparable study populations and nonstandardized assay techniques. [15][16][17][18][19][20][21][22][23] Up-to-date, critical care-derived scoring systems and biochemical markers have not been shown to be reliable for indicating infection and associated sepsis in patients with secondary peritonitis. 24 Currently, radiologic imaging procedures (eg, contrast-enhanced computed tomography) and guided aspiration techniques (eg, fine-needle aspiration) are frequently used to diagnose septic abdominal complications.…”
mentioning
confidence: 99%
“…Kinetic studies demonstrated CRP levels elevate on post-operative day (POD) 1, peak from POD2 to POD3, and decline by POD5 provided that there is no complication or infection. Four reports suggest a persistent threshold of greater than 100 mg/L might indicate abscess/septic complications [254][255][256][257]; other studies have refuted this conclusion, leaving uncertainty for clinical utility [258][259][260][261][262].…”
Section: Statement 44mentioning
confidence: 99%